THE EFFECT OF EQUALIZATION OF CIVIL SERVANT POSITIONS ON CAREER PATTERNS IN HR MANAGEMENT DEVELOPMENT - Aslami, Fathia; Sukmawati, Nur; Alfisyahri, Nuriah; Lestiyani, Tri Endah Karya (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2023)
The efforts of the Ministry of Administrative and Bureaucratic Reform to simplify the bureaucracy by changing structural positions into functional positions aim to create an agile, professional and dynamic bureaucratic environment that will increase the effectiveness and efficiency of government performance in providing public services. ASN and the organization need to make a number of modifications when implemented. The purpose of this paper is to document how the adoption of bureaucratic streamlining has affected the career development of ASN who have switched professions. Civil servants who transfer administrators from Echelon III and supervisors from Echelon IV to functional positions become the subject of writing. Descriptive analysis is used in the qualitative research methodology throughout the orientation and exploration phases, with an emphasis on a literature review approach adopted from official news websites, academic journals, and other sources deemed relevant used to compile information findings from a compilation of literature related to Resource Management. Human Resources (MSDM). In the structure of the PANRB Ministry over the past year, the implementation of the transition from structural positions to functional positions has not directly affected ASN career growth. The reason is that the ASN and the PANRB Ministry organizations still need to overcome a number of difficulties related to change. However, not all career growth patterns for functional jobs are available, although general ASN career development patterns are intended to be created. Organizational structure is another factor that counts for career advancement in functional roles. This factor is expected to have an impact on improving ASN careers at the Ministry of Administrative and Bureaucratic Reform in the future.